Boxing practitioners physiology review 1. Kinanthropometric parameters, skeletal muscle recruitment and ergometry - Nsengu Tshibangu, A. M. (Open Journal of Molecular and Integrative Physiology, 2020)
Seven percent voluntary body weight decrease by boxers requires 21 days while 4.4 percent increase needs only one day. Energy and fluid intakes reduction does not affect boxers punching force. Boxers effective punch masses and body weights correlate. Wrist girths and competition rankings of boxers correlate. Boxers show leanness body fat percentage. Boxers, generally highly mesomorphic, with increasing body weight, show ectomorphy decreases but endomorphy and mesomorphy increases. Vibration treatment enhances power in boxers arm flexors. Presence, nature and thickness of bandages and gloves donned influence boxers punch force. Stance posture adopted by boxers ends in locomotion functional parameters adaptations. Muscular recruitment sequence during rear straight punches may be influenced by the target height (head or body levels) and the boxer intention (produce maximal force or maximal speed). Handgrip strength: 1) increases from younger to older and from lighter to heavier boxers, and 2) correlates with competition ranking. Rear knee extension increases rear straight punching force to the head. Compared to uppercut and straight punches, the hook produces the highest change in hand velocity. Maximal forces are larger for the rear than the lead hand, and greater in more than in less experienced boxers. Hook punch force is greater than those of uppercut and straight punches. Boxer aim (produce maximum force or maximum speed) influence his punching force. Massage neither prevents a decrement in repeated performance nor has detrimental effects on performance, but increases recovery perceptions, compared with the passive rest intervention.